2020
DOI: 10.1186/s12913-020-05240-3
|View full text |Cite
|
Sign up to set email alerts
|

European Union training programme for tuberculosis laboratory experts: design, contribution and future direction

Abstract: Background: Tuberculosis (TB) control programmes rely heavily on laboratories to support both clinical care and public health. Qualified personnel with adequate technical and managerial skills comprise an integral component of any quality assured laboratory. Training a new generation of TB laboratory specialists was identified as a critical priority in the European Union /European Economic Area (EU/EEA). A tailored training programme for TB reference laboratory professionals was developed and implemented withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Many health systems in the Globe depend on clinical, o cial and governmental efforts without considering other implementation research settings against tuberculosis defeating (24). Although the recent health managerial policies of disease control were successful in the treatment of the disease but they failed in eradication (particularly the MDR tuberculosis) due to the lack of effective implementation research studies and trials (25)(26)(27). The present study showed the impact of a new empirical, managerial and integrated system for tuberculosis treatment in Sudan using innovative strategies of implementation research and how it is suitable for other countries who have similar conditions of disease epidemiologic.…”
Section: Direct Health Impact Outcomementioning
confidence: 99%
“…Many health systems in the Globe depend on clinical, o cial and governmental efforts without considering other implementation research settings against tuberculosis defeating (24). Although the recent health managerial policies of disease control were successful in the treatment of the disease but they failed in eradication (particularly the MDR tuberculosis) due to the lack of effective implementation research studies and trials (25)(26)(27). The present study showed the impact of a new empirical, managerial and integrated system for tuberculosis treatment in Sudan using innovative strategies of implementation research and how it is suitable for other countries who have similar conditions of disease epidemiologic.…”
Section: Direct Health Impact Outcomementioning
confidence: 99%